2012
DOI: 10.1111/j.1750-3841.2012.02684.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hilA in Response to Mild Acid Stress in Salmonella enterica is Serovar and Strain Dependent

Abstract: Salmonella enterica is the leading cause of foodborne illness with poultry and poultry products being primary sources of infection. The 2 most common S. enterica serovars associated with human infection are Typhimurium and Enteritidis. However, Kentucky and Heidelburg and the 2 most prevalent serovars isolated from poultry environments. Given the prevalence of other serovars in poultry products and environments, research is needed to understand virulence modulation in response to stress in serovars other than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The second virulence gene evaluated in this study, hilA, regulates the expression of invasion genes in response to environmental stimuli including osmolarity, oxygen levels, and pH (Durant et al, 2000;Fluit, 2005;Chuanchuen et al, 2010;Park et al, 2011;Gonzalez-Gil et al, 2012). In the present study, there was an overall negative correlation between survival and upregulation of these 2 genes indicating that perhaps efforts for virulence were shifted away from these genes and instead focused on upregulation of stress responses (Gonzalez-Gil et al, 2012).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The second virulence gene evaluated in this study, hilA, regulates the expression of invasion genes in response to environmental stimuli including osmolarity, oxygen levels, and pH (Durant et al, 2000;Fluit, 2005;Chuanchuen et al, 2010;Park et al, 2011;Gonzalez-Gil et al, 2012). In the present study, there was an overall negative correlation between survival and upregulation of these 2 genes indicating that perhaps efforts for virulence were shifted away from these genes and instead focused on upregulation of stress responses (Gonzalez-Gil et al, 2012).…”
Section: Discussionmentioning
confidence: 73%
“…All quantitative reverse-transcription real-time PCR (qRT-PCR) reactions were performed as described by Gonzalez-Gil et al (2012) using the ABI 7100 RT-PCR system (Applied Biosystems, Carlsbad, CA). Briefly, a 20-µL total volume consisted of 10 µL of Power SYBR Green PCR Master Mix (Life Technologies Corporation, Carlsbad, CA), 300 nM of each primer, 100 ng of cDNA template, and water to volume.…”
Section: Quantitative Reverse-transcription Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Using quantitative reverse transcriptase real-time PCR, Gonzalez-Gil et al reported that expression of the virulence gene regulator hilA was both serovar and strain dependent when isolates were exposed to either mild acetic or HCl acid stress. Responses were dependent on the type of acid used and were time dependent, with hilA being upregulated after a 2-h exposure to the respective acid (350). When Milillo et al compared S. Typhimurium transcriptome responses to sodium acetate and sodium propionate exposure after 1 min (55°C at pH 4.0), the respective gene expression patterns were similar, with no increases in expression levels of rpoS, phoPQ, or virulence factors despite their established roles in organic and inorganic acid stress (35,327,328,338).…”
Section: Salmonella Virulence Response and Organic Acidsmentioning
confidence: 99%
“…In their research, González et al (2012) compared hilA gene expression in response to acid stress between different Salmonella serovars and strains. Results showed that there are serovar and strain differences in virulence gene expression and acid tolerance; regulation of hilA showed to be serovar and strain dependent as well as dependent on acid type (González et al, 2012). In an extensive genome analysis comparison between UK-1 and other S. Typhimurium strains, Luo et al (2012) reported that virulence factors pertaining to one strain might increase or decrease virulence when present in a different strain.…”
Section: Resultsmentioning
confidence: 99%